2014
DOI: 10.1017/s0958344014000226
|View full text |Cite
|
Sign up to set email alerts
|

Affect and willingness to communicate in digital game-based learning

Abstract: The possible benefits of digital games for language learning and teaching have received increasing interest in recent years. Games are said, amongst others, to be motivating, to lower affective barriers in learning, and to encourage foreign or second language (L2) interaction. But how do learners actually experience the use of games? What impact does gameplay have on students’ perceptions of themselves as learners, and how does this affect their learning practice? These questions are important as they are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 57 publications
8
94
0
2
Order By: Relevance
“…The study also shows that a diverse use of IDLE activities by participants contributed to greater WTC online and higher productive vocabulary scores. This study echoes previous studies regarding the effects of digital games on both WTC (Reinders & Wattana, ) and productive vocabulary (Sundqvist & Wikström, ; Sylvén & Sundqvist, ). However, this study offers new insights into how the quality (or diversity) of out‐of‐class digital English learning, not quantity (or total amount) of such kind, can be particularly beneficial to those outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study also shows that a diverse use of IDLE activities by participants contributed to greater WTC online and higher productive vocabulary scores. This study echoes previous studies regarding the effects of digital games on both WTC (Reinders & Wattana, ) and productive vocabulary (Sundqvist & Wikström, ; Sylvén & Sundqvist, ). However, this study offers new insights into how the quality (or diversity) of out‐of‐class digital English learning, not quantity (or total amount) of such kind, can be particularly beneficial to those outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Although this field of inquiry is still in its beginning stages, findings from recent studies suggest a positive correlation between IDLE and English learning outcomes, such as vocabulary development and self-reported English proficiency (Dressman, Lee, & Sabaoui, 2016;Sundqvist & Sylv en, 2014;Sundqvist & Wikstr€ om, 2015;Sylv en & Sundqvist, 2012). Additional studies have also implied that IDLE could contribute to affective and cognitive domains such as willingness to communicate and English test grades and confidence (e.g., Butler, Someya, & Fukuhara, 2014;Lai, Zhu, & Gong, 2015;Reinders & Wattana, 2015).…”
mentioning
confidence: 99%
“…Additionally, interactions with native speakers in anonymous informal gaming environment reduced anxiety and increased exposure to slang [29] [30] and colloquial language [25]. Nevertheless, researchers expressed concern that "the exposure to informal registers" and "the incorporation of grammatically incorrect forms remains a potential risk for learner participation in MMORPGs (…) where access is provided to native speaker interlocutors" [30] as it may affect the accuracy and complexity in a target language production [47]. To reduce the side effects of interactions with native speakers, learners should get scaffolding instructions.…”
Section: Effective Strategiesmentioning
confidence: 99%
“…Due to a high interactivity of video games, note taking [43] and media [49] strategies did not provide enough support for vocabulary learning. A number of researchers revealed that learners experienced confusion with game mechanics as a result they could not focus on language learning [24] [26] [30] [32] [37] [47]. However, this ability enhanced through the mastery in gaming.…”
Section: Less Effective Strategiesmentioning
confidence: 99%
“…10 In the US, gaming is reported to be even more popular and more demographically equalized than in Europe. 11 The benefit of Digital Game-Based Language Learning (DGBLL) has increased significantly in recent years and has received considerable attention in recent computer-assisted language learning (CALL) studies 12 . Students who used computer games or interactive simulations showed better results in cognitive gains and attitudes toward learning than those who experienced traditional instruction.…”
Section: Introductionmentioning
confidence: 99%